Improved neonatal outcomes by multidisciplinary simulation—a contemporary practice in the demonstration area of China - Xu, Chenguang; Zhang, Qianshen; Xue, Yin; Chow, Chun-Bong; Dong, Chunxiao; Xie, Qian; Cheung, Po-Yin (Frontiers in Pediatrics, 2023)
Background: Simulation-based training improves neonatal resuscitation and decreases perinatal mortality in low- and middle-income countries. Interdisciplinary in-situ simulation may promote quality care in neonatal resuscitation. However, there is limited information regarding the effect of multidisciplinary in-situ simulation training (MIST) on neonatal outcomes. We aimed to investigate the impact of MIST on neonatal resuscitation in reducing the incidence of neonatal asphyxia and related morbidities. Methods: Weekly MIST on neonatal resuscitation has been conducted through neonatal and obstetrical collaboration in the University of Hong Kong-Shenzhen Hospital, China, since 2019. Each simulation was facilitated by two instructors, performed by three health care providers from obstetric and neonatal intensive care units, followed by debriefing of the participants and several designated observers. The incidence of neonatal asphyxia, severe asphyxia, hypoxic-ischemic encephalopathy (HIE) and meconium aspiration syndrome (MAS) before (2017-2018) and after (2019-2020) the commencement of weekly MIST were analyzed. Results: There were 81 simulation cases including the resuscitation of preterm neonates of different gestational ages, perinatal distress, meconium-stained amniotic fluid, and congenital heart disease with 1503 participant-counts (225 active participants). The respective incidence of neonatal asphyxia, severe asphyxia, HIE and MAS decreased significantly after MIST (0.64%, 0.06%, 0.01% and 0.09% vs. 0.84%, 0.14%, 0.10% and 0.19%, respectively, all p<0.05). Conclusions: Weekly MIST on neonatal resuscitation decreased incidence of neonatal asphyxia, severe asphyxia, HIE and MAS. Implementation of regular resuscitation simulation training is feasible and may improve the quality of neonatal resuscitation with better neonatal outcomes in low- and middle-income countries.